Sizing Analysis and Cost Optimization of Hybrid Solar-Diesel-Battery Based Electric Power Generation System Using Simulated Annealing Technique - Agarwal, Nitin; Kumar, Anoop; Feng, Varun (Distributed Generation & Alternative Energy Journal, 2012)
An optimization model has been developed to determine specifications of a hybrid solar-diesel-battery based power generation system to maintain an optimum tradeoff between the life cycle cost and CO2 emission from the system. The model has been solved by using the simulated annealing technique. The proposed method has been applied to a residential colony of 135 houses in Moradabad district, India. The optimum sizing process is verified by carrying out an appropriate sensitivity analysis. Simulation results shows that PV inclusion of 89% and diesel fraction of 11% with PV arrays of 1030 m2, 477 batteries of 24 V and 150 Ah and three diesel generators of 5 kW each is the optimized configuration having minimum a life cycle cost (LCC) of 973000 for 25 yrs, CO2 emission of 24193 kg/year and annual diesel consumption of 86212 liter. The model has been validated by comparing results with earlier research work. Keywords: CO2 Emission, Hybrid System, Life Cycle Cost, Optimization, Moradabad, Simulated Annealing, Solar-Diesel.